PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN (AUDIO VISUAL) TERHADAP HASIL BELAJAR MAHASISWA PADA MATA KULIAH PANCASILA PRODI PENDIDIKAN GURU SEKOLAH DASAR UNIVERSITAS NEGERI GORONTALO - Nurainun, Nurainun; Riandhana, Taufiq Eka; Aries, Nur Sakinah; Monoarfa, Fidyawati; Ismail, Reska Putri; Halifah, Nur; Efendi, Efendi (SINERGI : Jurnal Riset Ilmiah, 2025)
This Study aims to determine the effect of using learning media (audio visual) on learning outcomes in Pancasila courses in students of the Elementary School Teacher Education Stud Program at Gorontalo State University. This research uses a pre-experimental design wich only includes one group or class that will be given tratmen, with one group pretest posttest design conducted on one group without a control or comparison group. The subjects in this study were students of the Elemntary School Teacher Education Study Program at Gorontalo State University who were programming Pancasila courses. Data were collected through pretest and posttest using objective test intruments (multipel choice) wich had been tested for validity and reliability. Data analysis was carried out using descriptive statistical techniquest to find out the average pretest and posttest learning outcomes of the experimental class and inferetial statistics to test the hypothesis, namely the research resaults test. Shows that the use of learning media (audio-visual) significantly influences students understanding and mastery of the Pancasila course.